Mitigation of Learning Management System Vulnerabilities using Penetration Testing Methods - Ridho Surya Kusuma; Rakhmat Prasetyo Agung Nugroho (Journal of Cyber Health and Computer, 2024)
This research delves into vulnerability testing of Learning Management Systems (LMS) using penetration methods, aiming to enhance the security resilience of LMS platforms against cyber threats. By employing a structured penetration testing framework encompassing stages such as reconnaissance, scanning, gaining access, maintaining access, and covering tracks, the study seeks to identify and address potential vulnerabilities within LMS systems. The research contributes to fortifying LMS platforms by simulating attacks and evaluating system weaknesses to provide insights for effective security enhancements